2016
DOI: 10.4068/cmj.2016.52.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Spectral-Domain Optical Coherence Tomography in Glaucoma and NAION

Abstract: The development of optical coherence tomography (OCT) has changed the clinical management of ophthalmic diseases by furthering the understanding of pathogenesis, as well as improving the monitoring of their progression and assisting in quantifying the response to treatment modalities in ophthalmic diseases. Initially, the two-dimensional configuration of the optic nerve head (ONH) and the thickness of the retinal nerve fiber layer (RNFL) were the main OCT structural parameters used in clinical management of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The retina is considered an extension of the central nervous system (CNS) and has gained attention in the research of neurodegenerative disorders 4,5 . In ophthalmic research, spectral domain-optical coherence tomography (SD-OCT) provides a non-invasive, objective, and reproducible measurement of retinal structures of the eye 6 . Retinal changes measured by OCT have been considered as useful biomarkers in several neurodegenerative diseases, including PD.…”
Section: Introductionmentioning
confidence: 99%
“…The retina is considered an extension of the central nervous system (CNS) and has gained attention in the research of neurodegenerative disorders 4,5 . In ophthalmic research, spectral domain-optical coherence tomography (SD-OCT) provides a non-invasive, objective, and reproducible measurement of retinal structures of the eye 6 . Retinal changes measured by OCT have been considered as useful biomarkers in several neurodegenerative diseases, including PD.…”
Section: Introductionmentioning
confidence: 99%
“…The use of optical coherence tomography (OCT) is becoming more common in research and the clinical management of patients with optic neuropathies, including NAION [ 14 ]. For example, spectral-domain OCT has helped elucidate the relative degree of involvement for each optic disc sector with respect to retinal nerve fiber layer swelling and functional loss in acute and non-acute phases of NAION, respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…-NA-AION animal models of both rodents and non-human primates, that utilize laser light to activate intravascular photoactive dye to induce capillary vascular thrombosis, have documented the final occurrence of ON axon loss and RGCs death by apoptosis [40]. Ischemia-induced RGC death seems to be mainly related to neurotrophin deprivation [40]; -human histopathological studies of acute NA-AION cases have shown coagulative necrosis of ONH axons and glial cells; in the chronic NA-AION phase, a severe axonal loss was histologically demonstrated [24][25][26]; -using OCT images, several authors have shown that, in comparison to healthy eyes, those affected by NA-AION in the chronic phase showed a significant reduction in peripapillary retinal nerve fiber layer (RNFL) thickness due to the evolution towards optic atrophy, and a significant reduction in the macular ganglion cell layers caused by retrograde maculopathy [41][42][43].…”
Section: The Hypothesized Pathogenetic Sequence In Na-aionmentioning
confidence: 99%
“…Furthermore, FAG images frequently show vasodilatation in the region of the OD spared from ischemia [11,15,27], supporting the hypothesis of the so-called "luxury perfusion" as an autoregulatory mechanism to increase OD perfusion in the presence of ischemia [17]; c. Optical coherence tomography (OCT): is a non-invasive exam that can offer extensive information about the architecture of the ONH. Even if diagnostic OCT features for NA-AION have not been yet recognized [3,45], OCT can be used to identify a disk-at-risk or OD drusen and to monitor the disease course, with the assessment of the OD edema or atrophy [37,41]. Previous authors have demonstrated that, in comparison with healthy eyes, those affected with NA-AION showed a significant increase in peripapillary RNFL thickness in the acute phase, due to the OD edema, and a significant reduction in the chronic phase due to the evolution towards optic atrophy [41].…”
Section: What Kind Of Tests May Be Useful For the Differential Diagno...mentioning
confidence: 99%
See 1 more Smart Citation